Falaj and Agreement - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani irrigation channel (qanat falaj) construction is very old. The identity of the original qanat builders is still debated by the research community. An Omani legend ties the existence of specific daudi falaj to the times of King Solomon of the Old Testament. Persian Achaemenid Shahs and Sasanian Shahs actively encouraged channel construction in the region. Whomever the original builders were, these systems have provided communities in the northern Omani interior with water for irrigation and domestic use for at least 1500–2000 years. Villages form microcosms in which a falaj organization has a clear social and economic structure, based on an accurate and fair system of water distribution. Over 3000 falaj are still very much in use, providing over one third of irrigation water today. Unlike meticulous regulation in Persia proper, Omani irrigation law was devoid of unnecessary legislation. Customary principles and Islamic law were consolidated into a harmonious whole. This was accomplished the Islamic legal scholars, the ulama. Fair dealing, consultation and collective responsibility created relative harmony at the level of the villages. Most disputes, if any, were settled in consultation with falaj officials, wakil and arif.
Keywords: Droit maritime – Oman

Ibadi Islam and the Imamate Tradition - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
The roots of Ibadism can be traced back to the times of the fourth and last of the rightly guided Caliphs, Ali Abi bin Talib. Two important secessions took place from the mainstream Sunni Islam during Ali’s time: that of the Shia and that of the Kharijite, a loose grouping of different sections from which also the Ibadis would emerge later on. Oman and North Africa became strongholds for the developing Ibadi school of thought. The North African Ibadi Rustamid Imamate lasted until 296 AH/909 AD when it was overthrown by the Shiite Fatimids. Since then, the Ibadi African communities formed isolated pockets in Algeria, Libya and Tunisia but were never able to establish an Ibadi imamate again. In Oman, matters were different as Ibadism became the unifying factor for the tribes. Later came the wars of independence from the central Caliphate with the establishment of Ibadi Imamates. Imamate governance signified the imposition of rule of law—like conditions in the country, after years of unchecked tribal rule. The Ibadi Imamate was a supra tribal state, in that its legitimacy and power derived directly from tribal support. Islamic governance was based on law, starting with the choice of the Imam by consultation. Islamic legal scholars, the ulama, and the Imamate officials would influence the Omani cultural landscape, encouraging consultation and fairness in the conduct of everyday affairs.
Keywords: Droit maritime – Oman

Introduction - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Negotiations that produce durable outcomes are rather rare in international negotiations, which are often viewed as a zero-sum game in which one’s success is tied to the other’s loss. The Iran nuclear deal, negotiated in 2015, is a case in point. The original deal was the product of unbalanced negotiations. The deal’s compliance pull resulted weak, making it relatively easy for President Donald Trump to pull the US out of the deal in 2018. The search for more constructive ways of negotiation led to the path that became this book. An example of inclusive negotiations that produce durable outcomes was found in Oman, a historical seafaring nation, situated on the southeast corner of the Arabian peninsula and bordered by the Arabian Sea and the Indian Ocean. In Oman, water is the lifeblood of all life. Inclusive agreements over irrigation channels developed into Omani culture over a considerable time span from custom, Ibadi Islamic principles and tribal law. The Omanis became known as the people of consultation, Ahl Al-Shura.
Keywords: Droit maritime – Oman

Oman Water Diplomacy Part I: The Beginnings of the Middle East Desalination Research Centre (MEDRC) - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani water diplomacy has its roots in the cultural landscape of the Omani society. Omani falaj communities formed microcosms in which principles of consultation, mediation and fairness developed over centuries into an internalized code of conduct whose influence would later extend also to the conduct on the nation’s foreing policy. Sultan Qaboos’ rise into power in 1970 signalled a significant break with the isolationist past. From then on, Omani foreign policies departed from dialogue, moderation and inclusion. With these cultural and political resources in the diplomacy toolkit, Oman was ready to take an active role at the Water Resources Working Group of the Middle East Peace Process. Omanis were well-placed to understand the implications of sufficient water supply for regional security. The desalination of sea water was considered to be the key for desert countries in the Middle East for finding new sources of supply of drinking water. The sharing of scientific and technological expertise became the goal of a small group of Omani water architects. A common effort, an international research centre on water desalination based in Muscat was beginning to take shape in the heated climate of international politics around the Arab-Israeli conflict.
Keywords: Droit maritime – Oman